Propulsion aerodynamics for a novel high-speed exhaust system - Tsentis, Spyros; Goulos, Ioannis; Prince, Simon A.; Pachidis, Vassilios; Zmijanovic, Vladeta (American Society of Mechanical Engineers (ASME), 2023)
A key requirement to achieve sustainable high-speed flight and efficiency improvements in space access, lies in the advanced performance of future propulsive architectures. Such concepts often feature high-speed nozzles, similar to rocket engines, but employ different configurations tailored to their mission. This paper presents a numerical investigation on the aerodynamic performance of a representative novel exhaust system, which employs a high-speed, truncated, ideal contoured nozzle and a complex-shaped cavity region at the base. Reynolds-Averaged Navier-Stokes computations are performed for a number of Nozzle Pressure Ratios (NPRs) and free stream Mach numbers in the range of 2.7 < NPR < 24 and 0.7 < M∞ < 1.2 respectively. The corresponding Reynolds number lies within the range of 1.06 · 106 < Red < 1.28 · 106 based on the maximum diameter of the configuration. The impact of the cavity on the aerodynamic characteristics is revealed by direct comparison to an identical non-cavity configuration. Results show a consistent trend of increasing base drag with increasing NPR for all examined M∞ for both configurations, owing to the jet entrainment effect. Cavity is found to have no impact on the incipient separation location of the nozzle flow. At conditions of M∞ = 1.2 and high NPRs, the cavity has a significant effect on the aerodynamic performance, transitioning nozzle operation to under-expanded conditions. This results in approximately 12% higher drag coefficient compared to the non-cavity case and shifts the minimum NPR for which the system produces positive gross propulsive force to higher values.
Keywords: Aerodynamics; Exhaust systems; Propulsion; Cavities; Nozzles; Drag (Fluid dynamics); Architecture; Computation; Flight; Flow (Dynamics); Mach number; Pressure; Reynolds number; Rocket engines; Separation (Technology); Sustainability